Cobalt Bis(dicarbollide) Alkylsulfonamides: Potent and Highly Selective Inhibitors of Tumor Specific Carbonic Anhydrase IX - Grüner, Bohumír; Kugler, Michael; El Anwar, Suzan; Holub, Josef; Nekvinda, Jan; Bavol, Dmytro; Růžičková, Zdeňka; Pospíšilová, Klára; Fábry, Milan; Král, Vlastimil; Brynda, Jiří; Řezáčová, Pavlína (ChemPlusChem, 2021)
Invited for this month's cover is a collaboration from three institutes from the Czech Academy of Sciences: Institute of Inorganic Chemistry, Institute of Organic Chemistry and Biochemistry, and Institute of Molecular Genetics, and the University of Pardubice. The cover picture shows a family of potent and selective CA IX inhibitors that combines the structural motif of a bulky inorganic cobalt bis(dicarbollide) polyhedral ion with a propylsulfonamido anchor group. Read the full text of the article at 10.1002/cplu.202000574.
Keywords: Neoplasms; nádory; karboanhydrasa IX; inhibitory karboanhydras; lidé; Carbonic Anhydrase Inhibitors; Carbonic Anhydrase IX; kobalt; Cobalt; Humans